Design and experimental analysis of a low-frequency resonant hybridized nanogenerator with a wide bandwidth and high output power density. (December 2019) - Salauddin, Md; Toyabur, R.M.; Maharjan, P.; Rasel, M. Salauddin; Cho, Hyunok; Park, Jae Yeong
Abstract: Scavenging mechanical energy from low-frequency vibrations is of great interest owing to the accessibility of these vibrations in the ambient environment. In this study, the design and experimental analysis of a low-frequency resonant hybridized nanogenerator (LFR-HN) with a wide bandwidth and high output power density is presented. The design includes the integration of an electromagnetic generator (EMG) and triboelectric nanogenerator (TENG); tests were conducted under excitation by a dynamic shaker and manual vibrations. The EMG part employs the Halbach magnet array (HMA) to improve its magnetic flux which decreases the total dimensions of the generator and increases the high power density in the low-frequency vibration process. The TENG part utilizes nanostructured polytetrafluoroethylene (PTFE) and Al structures nanopores structures to increase the output performance. The fabricated LFR-HN exhibited a resonant frequency and wide bandwidth of 31.8 Hz (EMG) and 19.4 Hz (TENG). In the vibration shaker test, the LFR-HN delivered a maximum average power of 2.61 mW at a load resistance of 850 Ω, corresponding to an average power density of 0.261 mW/cm 3 at the resonance frequency of 18 Hz and under an acceleration of 0.85 g. In addition, manual vibration analysis of the LFR-HN was conducted under conditions including a hand banging the table, leg stomping the floor, regular walking, and a hand directly banging the LFR-HN; the average measured output power densities were 0.112 mW/cm 3, 0.071 mW/cm 3, 0.036 mW/cm 3, and 0.158 mW/cm 3, respectively. The fabricated LFR-HN demonstrates a significantly higher power density than that reported in previous studies. This study reports an essential step toward using low-frequency vibrations to power vibration sensors and portable and wearable electronic devices; LFR-HN is expected to be broadly applicable in our society. Graphical abstract: Image 1 Highlights: Modeling and experimental analysis of low frequency resonant hybridized nanogenerator. Combined mechanism of electromagnetic generator and triboelectric nanogenerator. Halbach magnet array, nano structure PTFE and nano porous structure. Wide bandwidth and high power density. Powered the vibration sensor, portable and wearable electronic devices applications.